Effect of charge self-consistency in DFT+DMFT calculations for complex transition metal oxides - Alexander Hampel; Sophie Beck; Claude Ederer (Physical Review Research, 2020)
We investigate the effect of charge self-consistency (CSC) in density-functional theory plus dynamical mean-field theory calculations compared to simpler “one-shot” calculations for materials where interaction effects lead to a strong redistribution of electronic charges between different orbitals or between different sites. We focus on two systems close to a metal-insulator transition (MIT), for which the importance of CSC is currently not well understood. Specifically, we analyze the strain-related orbital polarization in the correlated metal CaVO_{3} and the spontaneous electronic charge disproportionation in the rare-earth nickelate LuNiO_{3}. In both cases, we find that the CSC treatment reduces the charge redistribution compared to cheaper one-shot calculations. However, while the MIT in CaVO_{3} is only slightly shifted due to the reduced orbital polarization, the effect of the site polarization on the MIT in LuNiO_{3} is more subtle. Furthermore, we highlight the role of the double-counting correction in CSC calculations containing different inequivalent sites.